Feasibility of the "cuff-sleeve" suture method in improving the uterine blood supply after radical trachelectomy: A retrospective analysis - Chunxian Huang; Shaodan Lin; Miaochun Xu; Aoshuang Cheng; Yunyun Liu; Zhongqiu Lin; Ming Gao; Huaiwu Lu (Elsevier, 2024)
Objective: To explore the feasibility of the "cuff-sleeve" suture method in improving the uterine blood supply after radical trachelectomy (RT). Study design: Patients in the "cuff-sleeve" (n = 25) and traditional group (n = 10) underwent computed tomography angiography (CTA) to evaluate the residual uterine blood supply pattern after the surgery, and the preoperative group patients (n = 20) underwent CTA before the procedure. Results: The uteri of the 20 patients in the preoperative group were all supplied by bilateral uterine arteries of average diameter, 2.25 ± 0.35 mm. The uterine artery-supplying, hybrid supplying, and ovarian artery-supplying patterns accounted for 40 %, 36 %, and 24 % in the "cuff-sleeve" group and 20 %, 50 %, and 30 %, respectively, in the traditional group. The average diameter of the uterine arteries among the uterine artery-supplying pattern in the "cuff-sleeve" group (1.98 ± 0.36 mm) was more extensive than that in the traditional group (1.73 ± 0.15 mm) (p = 0.049). As also, the ovarian artery diameter of the hybrid supplying pattern in the "cuff-sleeve" group (1.65 ± 0.25 mm) was significantly larger than that in the traditional group (1.50 ± 0.35 mm) (p = 0.010). Additionally, while the pregnancy rate in the "cuff-sleeve" group (50.0 %) was higher than that in the traditional group (25.0 %), this difference was not statistically significant. Conclusions: The "cuff-sleeve" suture method was associated with increased diameter of the uterine and ovarian vessels and may be a feasible method to improve the uterine blood supply and pregnancy rate after radical trachelectomy. It still warrants further evaluation for both fertility and oncologic outcomes.